2015
DOI: 10.4037/ajcc2016789
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction With Elimination of all Visitation Restrictions in a Mixed-Profile Intensive Care Unit

Abstract: Background Open and patient-tailored guidelines have been recommended as the preferred visitation model in critical care settings; however, many critical care units continue to restrict visitation. Objectives To determine whether a transition from minimally restrictive to unrestricted visitation hours improves satisfaction of patients' family members and whether such a transition affects nurses' satisfaction and nurses' perceptions of satisfaction among patients' families. Methods Using a prospective, observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 14 publications
(22 reference statements)
0
46
0
5
Order By: Relevance
“…Many hospitals throughout the country have opened their ICUs to visitors in attempts to improve patient satisfaction scores (Liu, Read, Scruth, & Cheng, ; Ramona, ; Chapman et al., ). Studies show patients in an ICU experience multiple benefits when their loved ones are close by (Hinkle & Fitzpatrick, ; Obringer, Hilgenberg, & Booker, ; Al‐Mutair, Plummer, Clerehan, & O'Brien, ; Wong, Liamputtong, Koch, & Rawson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many hospitals throughout the country have opened their ICUs to visitors in attempts to improve patient satisfaction scores (Liu, Read, Scruth, & Cheng, ; Ramona, ; Chapman et al., ). Studies show patients in an ICU experience multiple benefits when their loved ones are close by (Hinkle & Fitzpatrick, ; Obringer, Hilgenberg, & Booker, ; Al‐Mutair, Plummer, Clerehan, & O'Brien, ; Wong, Liamputtong, Koch, & Rawson, ).…”
Section: Introductionmentioning
confidence: 99%
“…The general literature on visitation focuses on other acute health conditions and shows that most family members have preferences about visitors, preferring immediate and extended family members over other visitors (Wu et al, 2015). Research on visitation for other acute health conditions shows that family caregivers attempt to support the patient during the hospital stay through physical presence and comfort (Chapman et al, 2016). Family caregivers’ perception that their physical presence is beneficial to the patient increases their desire to be physically present with the patient on regular and frequent basis (Chapman et al, 2016).…”
Section: Families’ Perceptions Of Visitors During the Hospital Staymentioning
confidence: 99%
“…Research on visitation for other acute health conditions shows that family caregivers attempt to support the patient during the hospital stay through physical presence and comfort (Chapman et al, 2016). Family caregivers’ perception that their physical presence is beneficial to the patient increases their desire to be physically present with the patient on regular and frequent basis (Chapman et al, 2016). As impairments caused by moderate-to-severe TBI often preclude the patient from being able to make decisions during the hospital stay (Steward et al, 2016) or to state their visiting preferences, family caregivers of these patients often make decisions about visitors on the patient’s behalf.…”
Section: Families’ Perceptions Of Visitors During the Hospital Staymentioning
confidence: 99%
“…The recommend model for family visiting in critical care is an unrestricted visiting guideline, which allows patients and families to personalize visitation (9). A recent study found that a change to unrestricted visitation from minimally restricted visitation improved family satisfaction in a large mixed-profile ICU (10). The change in visitation to unrestricted visiting also improved the nurse's perceptions of family satisfaction with no associated change in nurse-reported interference with clinical care (10).…”
mentioning
confidence: 96%
“…A recent study found that a change to unrestricted visitation from minimally restricted visitation improved family satisfaction in a large mixed-profile ICU (10). The change in visitation to unrestricted visiting also improved the nurse's perceptions of family satisfaction with no associated change in nurse-reported interference with clinical care (10). To improve patient and family satisfaction, it is imperative to remove barriers such as restricted visitation to create open engagement and inclusion of families in medical decision making and care of their loved one (11).…”
mentioning
confidence: 98%